2016
DOI: 10.1136/gutjnl-2015-311049
|View full text |Cite
|
Sign up to set email alerts
|

Barriers against split-dose bowel preparation for colonoscopy

Abstract: NCT02287051; pre-result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
47
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 23 publications
0
47
0
1
Order By: Relevance
“…21,22 Other results showing that split-dose preparation was superior to day-before cleansing may have been caused by different time intervals between bowel cleansing and the examination. [23][24][25] In this study, it is possible that as all OSS regimens were prepared in a split-dose, this provided higher cleaning quality than PEG-AA, which was mainly prepared as a single-dose. The interval between the last dose of bowel preparation and the start time of colonoscopy would be helpful for the comparison.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Other results showing that split-dose preparation was superior to day-before cleansing may have been caused by different time intervals between bowel cleansing and the examination. [23][24][25] In this study, it is possible that as all OSS regimens were prepared in a split-dose, this provided higher cleaning quality than PEG-AA, which was mainly prepared as a single-dose. The interval between the last dose of bowel preparation and the start time of colonoscopy would be helpful for the comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the increased time and required morning of commitment, our study suggests that split-dose preparation would be more likely to interfere with domestic responsibilities and existing morning medication regimens. Another recent study assessing split-dose regimen uptake also found that social factors, including morning appointments, travel time to endoscopy, and low education level, were associated with limited uptake of the split-dose regimen [ 31 ]. It may be important for health systems and providers to specifically address these social barriers to ensure bowel preparation tolerability, given that split-dose is currently the standard of care.…”
Section: Discussionmentioning
confidence: 99%
“…Split-dose for morning procedures has been shown to improve ADR and especially the quality of the preparation in the right bowel [27,28] . Although, this scheme is advocated by major societies [29,30] , its uptake has been suboptimal due to factors such as fear of increased aspiration risk, fecal incontinence, and low patient education [31] , even with the ASA guidelines advocating a 2-hour clear liquid fast for all forms of anesthesia in patients without risk factors for aspiration [32] .…”
Section: Discussionmentioning
confidence: 99%